Pengaruh Pemberian Campuran Jahe Merah, Bawang Putih, Cuka Anggur Dan Madu Terhadap Kadar Kolesterol Total Dan Histopatologis Pembuluh Darah Aorta Jantung Tikus Putih Jantan - Rahimatul Uthia; Surya Dharma; Friska Mulya Dewita (STIFARM Padang, 2016)
Study of the effect of red ginger (Zingiber officinale Roscoe), garlic (Allium sativum L.), wine vinegar, and honey have been carried out on total cholesterol levels by using the tool Easy Touch GCHb and histopathological tests on male rats. The assortment of were given orally for 28 days with a dose of red ginger 0.162 g/kg BB, garlic 0,09 g/kg BB, wine vinegar 0.27 g/kg BB, and the honey of 1.8 g/kg BB. The data were analyzed by one-way ANOVA followed by Duncan test. The results showed a decrease in total cholesterol levels and may improve lumen area and lower scores damage to the blood vessels were significant (P <0.05), which means the provision of a assortment of red ginger (Zingiber officinale Roscoe), garlic (Allium sativum L.), wine vinegar and honey can lower total cholesterol and improve lumen area and lower scores damage to the blood vessels.